(3Md eTcdGJ GdETGQGJs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3hHYO aceG Cf Cced GdeYGQa hGLdgG TCfG hGUOb GdYdhe hChKbgG HjGfkG s
(3BNQgG (B:s
(3aEPG YQa Cf GdebOeGJ ef GdCUfGa GdePchQI ai GdfgL s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdGeHQhRjGfG (B(116) s
Keywords: (3GdadSaI hGdefWbs